Current and Future Anatomical and Functional Imaging Approaches to Pheochromocytoma and Paraganglioma - Timmers, H.J.L. M.; Taieb, D.; Pacak, K. (Hormone and Metabolic Research, 2012)
After establishing a biochemical diagnosis, pheochromocytomas and extra-adrenal paragangliomas (PPGLs) can be localized using different anatomical and functional imaging modalities. These include computed tomography, magnetic resonance imaging, single-photon emission computed tomography (SPECT) using 123I-metaiodobenzylguanidine or 111In-DTPA-pentetreotide, and positron emission tomography (PET) using 6-[18F]-fluorodopamine (18F-FDA), 6-[18F]-fluoro-l-3,4-dihydroxyphenylalanine (18F-DOPA), and 2-[18F]-fluoro-2-deoxy-d-glucose. We review the currently available data on the performance of anatomical imaging, SPECT, and PET for the detection of (metastatic) PPGL as well as parasympathetic head and neck paragangliomas. We show that there appears to be no ‘gold-standard’ imaging technique for all patients with (suspected) PPGL. A tailor-made approach is warranted, guided by clinical, biochemical, and genetic characteristics. In the current era of a growing number of PET tracers, PPGL imaging has moved beyond tumor localization towards functional characterization of tumors.
Keywords: FDG PET; MIBG scintigraphy; FDOPA PET; FDA PET